2017
DOI: 10.1002/qj.3005
|View full text |Cite
|
Sign up to set email alerts
|

Investigating raindrop size distributions in the (L‐)skewness–(L‐)kurtosis plane

Abstract: Skewness–kurtosis (β3−β4) and L‐skewness–L‐kurtosis (τ3−τ4) planes are proposed here as diagnostic tools to guide the identification of drop size distributions (DSDs) of rainfall at the ground. Firstly, we have determined β3−β4 and τ3−τ4 domains of 13 distribution families, namely normal, exponential, gamma, truncated gamma, log‐normal, truncated log‐normal, Weibull, hyperbolic, generalized hyperbolic, log‐logistic, skewed Laplace, Johnson SB and Johnson SU. These include those most used to represent DSDs and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…This plane was introduced by (Craig, 1936) and then updated by various authors, e.g. (Balakrishnan et al, 1994) and (Cugerone and De Michele, 2017). The skewness-kurtosis (β 3 − β 4 ) plane presents the skewness (Eq.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…This plane was introduced by (Craig, 1936) and then updated by various authors, e.g. (Balakrishnan et al, 1994) and (Cugerone and De Michele, 2017). The skewness-kurtosis (β 3 − β 4 ) plane presents the skewness (Eq.…”
Section: Data Analysesmentioning
confidence: 99%
“…The great flexibility and versatility of this distribution, together with its boundedness (which matches the physical limitations of the analysed aerosol particles) make the Johnson SB a good candidate for this purpose. The use of this distribution has also been inspired by (Cugerone and De Michele, 2015;D'Adderio et al, 2016); and (Cugerone and De Michele, 2017), where the authors have recently demonstrated the accuracy of this probability function in modelling the number size distribution of drops at the ground, a particular case of PNSD. Furthermore, the outcomes of this study are in accordance with the works of (Yu and Standish, 1990) and (Liu and Liu, 1994), in which JSB was firstly proposed for this aim.…”
Section: Introductionmentioning
confidence: 99%